Achilles tendon compliance influences tendon loading more than Achilles tendon twist in Achilles tendinopathy: a musculoskeletal modeling approach - Mylle, Ine; Funaro, Alessia; Crouzier, Marion; Bogaerts, Stijn; Vanwanseele, Benedicte (Frontiers in Bioengineering and Biotechnology, 2024)
The Achilles tendon exhibits anatomical variations in subtendon twist among individuals, and its compliance can change due to conditions like Achilles tendinopathy. However, current musculoskeletal models overlook these material and morphological variations. This study aimed to investigate the impact of altering Achilles subtendon insertion points and compliance on the triceps surae muscle forces, and therefore tendon loading, during dynamic exercises in one Achilles tendinopathy patient. Firstly, subtendon insertion points were altered in the musculoskeletal model based on a subject-specific 3D freehand ultrasound model and for three types of subtendon twist: low, medium, and high. Secondly, tendon compliance was modelled based on experimental values creating three musculoskeletal models: compliant, mean and stiff. Results indicated that tendon compliance had a larger effect than tendon twist on triceps surae muscle forces. Altering subtendon insertion points to the three types of twist showed a maximal change in muscle force contribution of 2.3% compared to the no-twist model. While during the eccentric rehabilitation exercisea common exercise choice during rehabilitationthe compliant tendon model showed substantial differences compared to the generic (control) musculoskeletal model, resulting in decreased gastrocnemius medialis (-3.5%) and gastrocnemius lateralis (-3.2%) contributions and increased soleus contribution (+6.6%). Our study results highlight the necessity of incorporating tendon compliance in musculoskeletal models to accurately predict triceps surae muscle forces, especially for individuals with increased tendon compliance, such as patients with Achilles tendinopathy. Such findings contribute to the development of more accurate predictions of muscle forces and hence, personalized rehabilitation strategies.